The Retrospect and Prospect of the Modern University Models: Russian Example - Gilyazova, Olga Sergeevna; Zamoshchanskaya, Anna Nikolaevna (Journal of History Culture and Art Research, 2019)
Many higher education theorists and practitioners agree that the university system is progressively becoming ineffective. The article explores the historical retrospect and prospect of the evolution of the modern university as a social institution, the successor of the medieval university and the university of the Modern Times. Humboldt’s idea of a university outlined the design of the modern European university model and became the underlying concept for the Russian higher school, which, as compared to Europe, did not have any medieval predecessor-universities. As we can see, the Humboldtian model of the university comes into conflict with the present-day cultural environment and with the processes taking place in higher education: commercialization, massification, bureaucracy, etc. These processes, together with such trends in education as globalization, informatization, cultural space networking, changing youth socialization, etc. urge the revision of the conceptual framework of the university model. The three former university models: corporate (medieval); classical (Humboldtian); modern (pedagogical) are being replaced by new models of the university of the future: the "Open (hybrid) University", the Third Generation University, the Entrepreneurial University, the Research University, etc. Great expectations are pinned on new technologies to overcome the crisis of the modern university system. However, they should not be seen as the panacea – the viewpoint adopted by some university authorities who are fast in employing IT innovations, though they are nothing but a mere tool of no inherent value. As a tool, they have their own benefits that should not gloss over their limitations.